Metabolic tumor volume and total lesion glycolysis as prognostic factors in head and neck cancer: Systematic review and meta‐analysis. Issue 12 (11th September 2020) - Rijo‐Cedeño, Jefferson; Mucientes, Jorge; Álvarez, Oscar; Royuela, Ana; Seijas Marcos, Sara; Romero, Jesús; García‐Berrocal, José Ramón
Abstract: The role of metabolic tumor volume (MTV) and total lesion glycolysis (TLG) in head and neck cancer (HNC) prognosis is not well established. We conducted a systematic review focusing on MTV and TLG measured by 18 F‐FDG positron‐emission tomography in HNC. Meta‐analyses were developed, estimating hazard ratios (HRs) for overall survival (OS) and disease‐free survival (DFS). Eighteen studies were found with a total of 1512 patients. MTV‐adjusted analysis had an HR of 4.65 (95% CI = 2.04‐10.6) for DFS and 3.89 (95% CI = 1.47‐10.30) for OS. TLG‐unadjusted analysis had an HR of 3.19 (95% CI = 2.33‐4.37) for DFS and 2.48 (95% CI = 1.82‐3.39) for OS. TLG‐adjusted analysis for DFS obtained an HR of 2.05 (95% CI = 0.96‐4.39). MTV and TLG are good prognostic factors in HNC, as high values predict a worse OS and DFS. Given the important information they provide, these parameters may be considered in clinical practice, as they are easily obtainable with current technology.